Social distraction? Social media use and political knowledge in two U.S. Presidential elections. (January 2019) - Lee, Sangwon; Xenos, Michael
Abstract: With increasing numbers of people using social media to get news and political information, whether social media helps users learn about politics has become an important question. Intrigued by the potential of social media to politically educate people, researchers have begun to explore the effects of social media on political knowledge. However, the findings from these studies have been far from conclusive. Drawing on both cross-sectional and panel data from two recent United States presidential elections, this study examines how political social media use and general social media use influence political knowledge. Overall, the results of the cross-sectional and panel analyses lead to the same conclusions. Both show that political social media use does not have a significant effect on political knowledge, while general social media use has a moderately negative effect on political knowledge. Thus, on balance, the overall impact of social media on political knowledge appears to be negative. Implications and directions for future research are discussed. Highlights: General social media use has a moderately negative effect on political knowledge. Political social media use does not have a significant effect on political knowledge. On balance, the overall impact of social media on political knowledge is negative. Findings hold consistent across two different U.S. presidential election cycles.